Authoritarian Leadership in Organizational Change and Employees’ Active Reactions: Have-to and Willing-to Perspectives - Du, Jing; Li, Nan Nan; Luo, Yuan Jing (Frontiers in Psychology, 2020)
Although prior studies has found the negative relation of authoritarian leadership with workplace outcome, authoritarian leadership styles are particularly prevalent in emerging business areas. This study examines the effectiveness of authoritarian leadership in organizational change by considering two boundary conditions: low perceived job mobility among employees in have-to exchange situations and high cognitive trust in leaders in willing-to exchange situations. Based on a sample of 203 employees and their supervisors in 39 work teams in China, multilevel modeling identified a negative impact of authoritarian leadership on employees’ active support for organizational change. However, this negative effect disappeared when perceived job mobility was low and cognitive trust in the leader was high. The findings offer insights into the prevalence of authoritarian leadership in emerging markets despite negative impressions of this leadership style (Harms et al., 2018).